Conservation status of Brazilian snakes inhabiting the Atlantic Forest of Northeastern Brazil - França, Rafaela C.; Solé, Mirco; França, Frederico G. R. (Frontiers in Ecology and Evolution, 2024)
Due to the high level of disturbance in natural ecosystems and the progressive loss of habitats resulting from anthropic occupation, biodiversity conservation represents one of the greatest challenges today. Red lists of threatened species are essential tools for identifying species at risk of extinction and guiding conservation efforts. In this study, we assessed the vulnerability to extinction of 55 snake species that occur in the Atlantic Forest of northeastern Brazil in Paraíba state. We developed vulnerability indices based on 12 factors known to influence the survival of snake populations. To analyze the threat profiles and relative risk levels within the snake community, we employed principal component analysis (PCA) and cluster analysis. Additionally, we compared our findings with existing red lists of threatened species. Our results reveal that only 18% of the snake fauna in this region is free of any threat. The aquatic species Helicops angulatus and Oxyrhopus trigeminus were the snakes that presented the lowest risk of extinction, while Caaeteboia gaeli and Crotalus durissus presented the highest risk of extinction. Two groups of species were considered non-threatened and five groups were considered threatened. Our study provides the first overview on the conservation status of snake species in the northern portion of the Atlantic Forest and contributes to a better evaluation of conservation planning for this group in the region.